MANAJEMEN PENDISTRIBUSIAN DAGING KURBAN DI MA’HAD AL-ZAYTUN - Infadzah Al Shidqi; Sobirin; Ahmad Asrof Fitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The management of sacrificial meat distribution in Ma’had Al-Zaytun is an important part of religious activities aimed at strengthening social relations and community welfare. The process includes meticulous planning, execution and evaluation to ensure fair and equitable distribution. The purpose of the research is to find out how the management of sacrificial meat distribution in Ma’had Al-Zaytun and to analyze the factors that support and hinder the distribution of sacrificial meat in Ma’had Al-Zaytun. The research method used in this study is a qualitative method. The research location is Ma’had Al-Zaytun. Data collection techniques through observation, interviews and documentation. The results showed that the management of qurbani meat distribution in Ma’had Al-Zaytun proved to be effective and right on target, and can be used as an example in managing distribution that involves various parties and resources efficiently. The success of qurbani meat distribution in Ma’had Al-Zaytun was supported by sufficient personnel, adequate fleet, and active participation of students and staff. Despite the challenges of distance and the amount of meat, the use of teak leaves as wrappers managed to maintain the quality of the meat until it reached the recipients. Keywords: Management, Qurbani Distribution, Ma’had;